Prevention of first-episode psychosis in people at clinical high risk: a randomized controlled, multicentre trial comparing cognitive-behavioral therapy and clinical management plus low-dose aripiprazole or placebo (PREVENT) - Bechdolf, Andreas; Müller, Hendrik; Hellmich, Martin; de Millas, Walter; Falkai, Peter; Gaebel, Wolfgang; Gallinat, Jürgen; Hasan, Alkomiet; Heinz, Andreas; Janssen, Birgit; Juckel, Georg; Karow, Anne; et al. (Schizophrenia bulletin, 2023)
There is limited knowledge of whether cognitive-behavioral therapy (CBT) or second-generation antipsychotics (SGAs) should be recommended as the first-line treatment in individuals at clinical high risk for psychosis (CHRp). To examine whether individual treatment arms are superior to placebo and whether CBT is non-inferior to SGAs in preventing psychosis over 12 months of treatment. PREVENT was a blinded, 3-armed, randomized controlled trial comparing CBT to clinical management plus aripiprazole (CM + ARI) or plus placebo (CM + PLC) at 11 CHRp services. The primary outcome was transition to psychosis at 12 months. Analyses were by intention-to-treat. Two hundred eighty CHRp individuals were randomized: 129 in CBT, 96 in CM + ARI, and 55 in CM + PLC. In week 52, 21 patients in CBT, 19 in CM + ARI, and 7 in CM + PLC had transitioned to psychosis, with no significant differences between treatment arms (P = .342). Psychopathology and psychosocial functioning levels improved in all treatment arms, with no significant differences. The analysis of the primary outcome transition to psychosis at 12 months and secondary outcomes symptoms and functioning did not demonstrate significant advantages of the active treatments over placebo. The conclusion is that within this trial, neither low-dose aripiprazole nor CBT offered additional benefits over clinical management and placebo.
Online veröffentlicht: 6. April 2023
Gesehen am 22.05.2024